2015 IEEE World Conference on Factory Communication Systems (WFCS) 2015
DOI: 10.1109/wfcs.2015.7160550
|View full text |Cite
|
Sign up to set email alerts
|

Time-synchronized Wireless Sensor Network for structural health monitoring applications in railway environments

Abstract: In this work a time-synchronized Wireless Sensor Network (WSN) has been designed and implemented for a realtime Structural Health Monitoring (SHM) system for trains. Channel measurements have been done in the first place on a real operational scenario, and obtained results have been used as inputs for the design of the physical layer of the WSN. A specific Time Division Multiple Access (TDMA) MAC layer and a synchronization algorithm have also been developed for allowing a deterministic data collection and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The propagation channel of these communications has been investigated in literature. An example of wireless channel measurement in order to characterize the propagation environment for inter-car communications is described in [ 10 ]. Moreover, a measurement and analysis of a channel considering the use of Trans European Trunked RAdio (TETRA) is presented in [ 11 ].…”
Section: Communication Systems In Railway Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation channel of these communications has been investigated in literature. An example of wireless channel measurement in order to characterize the propagation environment for inter-car communications is described in [ 10 ]. Moreover, a measurement and analysis of a channel considering the use of Trans European Trunked RAdio (TETRA) is presented in [ 11 ].…”
Section: Communication Systems In Railway Scenariosmentioning
confidence: 99%
“…Another real-time WSN-based railway SHM system is presented in [ 10 ]. In such an article the researchers focused on designing a customized MAC layer and a synchronization algorithm.…”
Section: Iot-enabled Services: From More Efficient Operations To Nmentioning
confidence: 99%
“…References Vehicle Frequency Bandwidth [11] Bus 2 + 5 GHz Passengers [12] Airplane [13] UWB [14] 2 + 5 GHz [15] Narrow band [16] 3-8 GHz UWB Passengers [17] 2 + 5 GHz [18] Wideband [19] UWB [ 2.45 GHz 100 MHz [26] 434 MHz Narrow band [27] Intravehicle [28] 2 GHz [29] 2.45 GHz Wideband Intervehicle measurements. For the large wide-body cabin of an A380 airplane with two aisles, [16] shows a reduced delay spread for UWB measurements between 3 and 8 GHz.…”
Section: Inside Vehiclementioning
confidence: 99%
“…In order to characterize the propagation environment for intervehicle communications, a wireless channel measurement campaign was carried out in [29]. This campaign was done at La Sagra maintenance facilities in Mocejón, Spain.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…This RFIC allows proprietary operation at 2 Mbps with FSK/GFSK modulation, as well as operation at 250 kbps using DSSS and OQPSK (therefore, compatible with the IEEE 802.15.4 standard). Measurements performed in [23] have indicated that spatial antenna diversity will need to be implemented to overcome flat fading in the targeted propagation environment. In this sense, a very interesting feature of ADF7242 is that it has a duplicated reception chain, which allows a straightforward implementation of antenna diversity techniques, as it is able to continuously monitor the received signals in both reception chains and select the optimum one.…”
Section: Radio Modulementioning
confidence: 99%